2018
DOI: 10.1016/j.optom.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Extended depth of focus contact lenses vs. two commercial multifocals: Part 2. Visual performance after 1 week of lens wear

Abstract: PurposeTo compare the visual performance of prototype contact lenses designed via deliberate manipulation of higher-order spherical aberrations to extend-depth-of-focus with two commercial multifocals, after 1 week of lens wear.MethodsIn a prospective, participant-masked, cross-over, randomized, 1-week dispensing clinical-trial, 43 presbyopes [age: 42–63 years] each wore AIROPTIX Aqua multifocal (AOMF), ACUVUE OASYS for presbyopia (AOP) and extended-depth-of-focus prototypes (EDOF) appropriate to their add req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Subjective benefits (quality of life) Presbyopia reduces vision related quality-of-life and although this can be improved with corrections, it cannot currently be restored to pre-presbyopic states (McDonnell et al, 2003). Standardised vision-related questionnaires generally include few items to assess near visual activities, concentrate on spectacle dependence only, are targeted to measure another aspect of vision (McAlinden et al, 2010), or have not been appropriately validated (Alio and Mulet, 2005;Alio et al, 2004;Bakaraju et al, 2018;Diec et al, 2017;Kohnen et al, 2017;Walkow et al, 1997;Wang et al, 2005). There is only one validated questionnaire available which specifically assesses near visual ability (Buckhurst et al, 2012a) and this is being updated to make it relevant to modern intermediate and near vision tasks such as smartphone and tablet use.…”
Section: 4mentioning
confidence: 99%
“…Subjective benefits (quality of life) Presbyopia reduces vision related quality-of-life and although this can be improved with corrections, it cannot currently be restored to pre-presbyopic states (McDonnell et al, 2003). Standardised vision-related questionnaires generally include few items to assess near visual activities, concentrate on spectacle dependence only, are targeted to measure another aspect of vision (McAlinden et al, 2010), or have not been appropriately validated (Alio and Mulet, 2005;Alio et al, 2004;Bakaraju et al, 2018;Diec et al, 2017;Kohnen et al, 2017;Walkow et al, 1997;Wang et al, 2005). There is only one validated questionnaire available which specifically assesses near visual ability (Buckhurst et al, 2012a) and this is being updated to make it relevant to modern intermediate and near vision tasks such as smartphone and tablet use.…”
Section: 4mentioning
confidence: 99%
“…Results from Fernandes et al [97] were within ±1 line of their reported VA for all the experimental conditions except for Monovision under near low contrast visual acuity (LCNVA), which performed better than Multifocal lens in their study. Recently, several clinical studies also evaluated visual performance with different contact lenses [103][104][105]107]. Bakaraju et al [103] measured the high contrast visual acuity (HCVA) and the low contrast visual acuity (LCVA) for the Airoptix Aqua, the Acuvue Oasys and extended depth of focus (EDOF) contact lens.…”
Section: Performance Of Contact Lenses For Presbyopia Correctionmentioning
confidence: 99%
“…Recently, several clinical studies also evaluated visual performance with different contact lenses [103][104][105]107]. Bakaraju et al [103] measured the high contrast visual acuity (HCVA) and the low contrast visual acuity (LCVA) for the Airoptix Aqua, the Acuvue Oasys and extended depth of focus (EDOF) contact lens.…”
Section: Performance Of Contact Lenses For Presbyopia Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used contact lenses have multifocal profiles and extended depth of focus (EDOF) profiles. 10,14,15 However, the profiles of contact lenses are frequently refractive with optical power distributed in central and annular zones, which leads to the undesirable dependence of lens performance on pupil size. For this reason, intraocular lenses are used more frequently when monovision is applied.…”
Section: Introductionmentioning
confidence: 99%